G Protein-Coupled Estrogen Receptor, GPER1, Offers a Novel Target for the Treatment of Digestive Diseases - DeLeon, Chelsea; Wang, David Q.-H.; Arnatt, Christopher K. (Frontiers in Endocrinology, 2020)
There are gender differences between men and women in many physiological functions and diseases, which indicates that female sex hormones may be important. Traditionally, estrogen exerts its biological activities by activating two classical nuclear estrogen receptors, ESR1 and ESR2 (ER and ER respectively). However, the roles of estrogen in the regulation of physiological functions and the pathogenesis of diseases become more complicated with the identification of the G protein-coupled estrogen receptor (GPER1). Although many GPER1-specific ligands have been developed, the therapeutic mechanisms of exclusively targeting GPER1 are not yet well understood. Translational applications and clinical trial efforts for the identified GPER1 ligands have been focused primarily on the reproductive, cardiovascular, nervous, endocrine, and immune systems. More recently, research found that GPER1 may play an important role in regulating the digestive system. Cholesterol gallstone disease, a major biliary disease, has a higher prevalence in women than in men worldwide. Emerging evidence implies that GPER1 could play an important role, independent of the classical ESR1, in the pathophysiology of cholesterol gallstones in women. This review discusses the complex signaling pathways of three estrogen receptors, highlights the development of GPER1-specific ligands, and summarizes the latest advances in the role of GPER1 in the pathogenesis of gallstone formation.